(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Pelvic Inflammatory disease is presented with different clinical presentation among the sexually active women. Objectives: The purpose of the present study was to see the clinical profiles of women presented with pelvic inflammatory diseases. Methodology: This cross-sectional study was carried out in the Department of Obstetrics and Gynaecology at Dhaka Medical College Hospital, Dhaka, Bangladesh from November 2001 to April 2002 during the period of six (06) months and December 2002 to February 2003 for three (03) months with the total duration of nine (09) months. Women at any age who were suffering from chronic pelvic inflammatory disease (PID) attended at the OPD of gynecology Department at Dhaka Medical College Hospital, Dhaka, Bangladesh were selected as study population. Epidemiological aspects and clinical presentation have been mainly highlighted in this study. Result: A total number of 150 cases were recruited for this study. Among 150 case of chronic pelvic inflammatory disease (PID) majority of the patients (54%) belonged to the age group of 26 to 35 years of age group followed by 16 to 25 years which was 33.3% cases. Majority 96.0% patients had pain in the lower abdomen; 78.6% cases had backache; 76.6% cases had dyspareunia; 64.0% had congestive dysmenorrhea and 60.0% cases had vaginal discharge. Regarding menstrual problems, 72.7% cases had dysmenorrhea. Majority (84.0%) cases were multipara. Conclusion: In conclusion lower abdominal pain, backache, dyspareunia, congestive dysmenorrhea are the major complaints among the PID patients. Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 129-132